The level of awareness of the community of Sibolga City and its surroundings about the Law on Child Protection - Syamriansyah Tanjung; Rajin sitepu (IHSA Institute, 2024)
This research is motivated by the fact that the rate of convictions is high in cases of criminal acts of violence against children. Data from the Sibolga City District Court, whose jurisdiction covers Sibolga City and its surroundings, shows that there have been 143 cases of violence against children in the last 6 years. The aim of this research is to analyze the level of awareness of the people of Sibolga City and its surroundings regarding the Child Protection Law. The method used in the research is empirical legal research (sociology) to see the level of awareness of the people of Sibolga City and its surroundings regarding child protection laws. The approach taken in this research was by distributing questionnaires using Google Form with the results of 89 respondents consisting of 58.4% women and 41.6% men with various jobs such as 67.4% in the private sector, 30 civil servants/ASNs. .3% and the rest is BUMN/BUMD. The results of this research show that the level of knowledge of the people of Sibolga City and its surroundings regarding the Child Protection Law is 93.3% aware that there is a law regarding child protection, 93.3% know about the existence of children's rights, 93.3% of parents do not have committed violence in the form of discrimination, neglect, exploitation of children, and 97.8% have an advisory attitude, meaning they do not commit violence against children who are naughty, rebellious, truant from school, and like to disturb their friends. So the conclusion that can be drawn from this research is that there is no correlation between the high level of violence against children that occurs and the level of legal awareness of the people of Sibolga City and its surroundings